Rekayasa Sistem Informasi Dengan Pendekatan Model Information Technology Infrastructure Library - Dadi Rosadi (STMIK Mardira Indonesia, Bandung, 2013)
Today, almost all the institutions/organizations/companies need information technology to support its business. However, not all institutions/organizations/companies have good IT blueprint, so it will be difficult to develop systems/technology owned by the same practice field. These difficulties will result from (1) There is no standard system architecture, development tools, database management system (DBMS), and document systems, (2) Database design is not referring to the rules of normalization (3), Design perangat exclusive software to hardware (4) Design software is very dependent on the organizational structure of the company (5) The difficulty of maintenance, repair system testing, system integration, (6) Development always starts from the beginning, instead of continuing the existing system. Almost all institutions that have many branch offices build their own apliksi branch office, so that there will be duplication of systems / applications are built, it will result from the amount of energy, time and costs, so that needs to be built a framework to develop (1) application (2) transaction systems, and (3) online system, as a guide to develop the next aplications. Keywords: technology; information; institutions; systems, frameworks, infrastructure library